New features of the pre-Islamic period in Meliha - Al Bedwawi, Maryam; Al-Leheabi, Saleh (Al-Adab Journal, 2025)
The research discusses one of the most important historical eras witnessed by the Meliha region, affiliated to the Emirate of Sharjah in the United Arab Emirates, which is the pre-Islamic era, as Meliha witnessed five different eras over a period of approximately 130 thousand years: the Paleolithic Age, the Neolithic Age, the Bronze Age, and the Iron Age. Finally, the last era of the pre-Islamic period, which is considered a distinctive period in the history of Meliha, as archaeological discoveries have shown that Meliha was able during that period to form a strong, independent, sovereign kingdom with its own center, political authority, and strong commercial relations with most of the trade centers in the Arabian Peninsula. Its relations even extended to reach the Roman Empire and the Greek islands, and it had its own currency, which was minted there. Like other kingdoms of the Arabian trade basin and the Arabian Peninsula, Meliha was influenced by the religions, beliefs and ideas that were prevalent in the region during the third and fourth centuries BC. This can be clearly seen through the religions embraced by the inhabitants of Meliha, the deities they sanctified and their impact on aspects of their religious life, their burial rituals for their dead and the style of construction of their graves. The research also discusses the most important aspects of political, social and economic life in Meliha during that period, which could be identified through the coins, utensils, weapons, buildings and others left behind by its inhabitants.